Individual Retirement Accounts and Other Retirement Savings Plans - Josephine Turner (EDIS, 2004)
For many years, Congress has recognized that saving for retirement is a worthwhile social goal and should be encouraged by the government. The federal government has encouraged the growth of private pension and savings plans through the use of various tax incentives. This publication will focus mainly on individual retirement accounts (IRAs), but other plans such as simplified employee pensions (SEPs), 401-K plans, and Keogh plans will be discussed, too. This document is FCS5258, one of a series of the Department of Family, Youth and Community Sciences, University of Florida, UF/IFAS, Gainesville 32611. First published: September 2003.